Funding the Transition from Pay-As-You-Go Pensions by Taking Capital Gains on Land - Mark A. Roberts (University of Copenhagen, Economic Policy Research Unit (EPRU), 2001)
The transition from unfunded pensions may impose a double burden on a transitional generation, which must both pay taxes to finance current pension liabilities and save for their own retirement. There are also economic gains which will accrue to future generations from increased rates of savings and capital accumulation. In an economy with land, traded as an asset, increased productivity will raise current and future rents, causing capital gains in the price of land, which may be taxed to alleviate the income tax burden on the transitional generation. For certain parameterizations, reform may be Pareto-improving.
Keywords: 330; Rentenfinanzierung; Umlageverfahren; Grundsteuer; Theorie